Wavelength effect on hole shapes and morphology evolution during ablation by picosecond laser pulses. (October 2016) - Zhao, Wanqin; Wang, Wenjun; Li, Ben Q.; Jiang, Gedong; Mei, Xuesong
Abstract: An experimental study is presented of the effect of wavelength on the shape and morphology evolution of micro holes ablated on stainless steel surface by a 10 ps Q-switched Nd:VAN pulsed laser. Two routes of hole development are associated with the visible (532 nm) and near-infrared (1064 nm) laser beams, respectively. The evolution of various geometric shapes and morphological characteristics of the micro holes ablated with the two different wavelengths is comparatively studied for other given processing conditions such as a laser power levels and the number of pulses applied. Plausible explanations, based on the light-materials interaction associated with laser micromachining, are also provided for the discernable paths of geometric and morphological development of holes under laser ablation. Highlights: Evolutions of hole shape ablated by visible beam were studied upon applied powers. Evolutions of hole shape induced by near-infrared were studied upon applied powers. Evolutions of hole Morphology drilled by two beams were comparative analyzed. Some related reasons on these evolutions were discussed.